VR-based product development process: opportunities and challenges in the automotive industry - Winkler, Ingrid; Murari, Thiago B.; Ferreira, Cristiano V.; Freitas, Fabio (Anais Estendidos do Simpósio de Realidade Virtual e Aumentada (SVR); 2022: Anais Estendidos do XXIV Simpósio de Realidade Virtual e AumentadaDO - 10.5753/svr_estendido.2022.226711, 2022)
In the product development, the success of a manufacturing strategy is achieved by specifying a manufacturing process that it can be produced with minimal impact. In the automotive industry, to detect late, i.e., already during manufacturing phase, issues on customers preferences on new vehicles, physical ergonomic issues, or problems on usability of a product has a high cost of correction and long the time to launch a new product. Thus, given the complexity of products that are under development, designers must perform a number of procedures to guarantee that the finished product fits customer demands and is accepted by the market. With the emergence of low-cost virtual reality devices, the automotive industry is adopting virtual reality for several engineering processes and support everyday engineering. The patent filings have boomed since 2016, in a technology space that is rapidly evolving, offering opportunities to enter an area while it is still young. Virtual reality benefits the product development process by saving costs and time, closing customers, improving interactions, avoiding prototype transportation, optimizing the assembly line, improving the performance and well-being of the user, mitigating hidden dangers, stimulating novel insights and increasing team collaboration, and feeling of engagement, among others. However, certain constraints must be overcome before the technology’s possibilities can be fully harnessed. The challenges faced by VR-based processes are the lack of realism due to unnatural tactile and visual interactions, latency and registration issues, communication difficulties between teams, unpleasant symptoms, issues on depth, haptic, motion and movement perceptions, cybersecurity, cybersickness, lack of intuitiveness, and partial control over the user’s moving around, among others. While there are still challenges to be addressed until industries can fully benefit from the technology’s potential and these constraints prevent virtual reality from fully replacing conventional automotive product development in the near future, it is a valuable contribution to the process. In this context, this work discusses the opportunities and challenges of virtual reality-based product development process in the automotive industry. A better knowledge on this subject may provide a reference for decision-makers, practitioners and researchers as they continue to develop innovative immersive solutions in the product development in the automotive industry.